Understanding The Interactions of Biomolecules with Fabrics for Improved Fabric Care - Roberts, Joseph William (2025)
The textile industry faces sustainability challenges, including premature clothing disposal and microplastic pollution. Fabric care products play a vital role in extending garment lifespan, with biologically derived formulations showing promise. However, the understanding of their mechanisms of action remains limited.